Urban Fragmentation in the Age of Digital Platforms：Rebuilding the Nearby in Guangzhou, China - WANG, XIAOYU (University of Waterloo, 2025)
In contemporary China, rapid urbanization and the rise of digital platforms have reshaped the urban landscape and urban life. Functional and highly ordered urban space, paired with highly efficient lifestyles has further intensified urban fragmentation and social isolation. The idea of the “nearby”, as defined by Biao Xiang, is not a fixed administrative boundary, nor as clearly defined as a formal community. It is a fluid space that shifts with our everyday experiences centered around the individuals. It is the space of opportunities in which to encounter complexity and difference, and yet it is quietly disappearing from daily life. This thesis focuses on Tianhe District in Guangzhou, studying the fragmentation of three contiguous urban fabrics: a university campus, a traditional urban village, and gated residential community. Although they are spatially adjacent, these fabrics are separated by tangible and intangible boundaries are not only physically dividing space, but also shaping how people access space, resources, and interaction with one another. Fences and access control, institutional policies, platform algorithms and social identity together reinforce these divisions. The study adopts a range of methods, site visits, mapping, and collage as analytic approaches, starting from specific social groups, the research identifies four social phenomena, each of which is then addressed through corresponding design interventions to activate urban boundary spaces, in order to rebuild everyday connections between socially and spatially divided urban communities. The thesis argues that design can help restore social diversity, and promote social resource sharing and empathy and resist our growing urban alienation.
Keywords: urban fragmentation; digital platform; boundaries; the nearby; urban village; university